Number 30 (December 1994) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1994)
(December 1994) - Notes on the Status and Life History of the Northern Madtom, Noturus stigmosus, in Mississippi. By G.R. Parson, 3 pp. New Distribution Records of Gulf Slope Drainage Fishes in the Ocmulgee River System, Georgia. By H.L. Bart, et al., 7 pp. Minutes, Regional Reports, Announcement.
Keywords: northern madtom; noturus stigmosus; mississippi; gulf slope drainage; ocmulgee river